Blockchain for IoT - Mukhopadhyay, Debarka (Boca Raton : Chapman & Hall/CRC Press, 2023)
"Blockchain for IoT provides the basic concepts of blockchain technology and its applications to varied domains catering to socio-technical fields. It also introduces intelligent blockchain platforms by way of infusing elements of computational intelligence into blockchain technology. With the help of an interdisciplinary approach, it includes insights into real-life IIoT applications to enable the readers to assimilate the concepts with ease. Salient features include the fundamentals of blockchain and the internet of things with special reference to the synergy between the two in yielding a robust and secure distributed data processing environment. State-of-the-art techniques, including integration of blockchain with IoT authentication, smart frameworks, decentralized autonomous organization (DAO), blockchain applications in intellectual property rights, chain of custody, individual property rights, and notary public verification are explored"--
OCLC-licensed vendor bibliographic record.
Keywords: Blockchains (Databases); Internet of things; COMPUTERS / Computer Engineering; COMPUTERS / Artificial Intelligence; COMPUTERS / Information Theory